Penerapan model discovery learning berbantuan media phet untuk meningkatkan kompetensi siswa - I Wayan Widia (Indonesian Journal of Educational Development, 2020)
This study aims to improve students’s knowledge and skills competency through the application of discovery learning assisted bt PhET (Physics Education And Technology) media in learning physics. This type of research is classroom action research, which consist of two cycles. This research was conducted at class XI IPA1 SMA Negeri 1 Tampaksiring involving 34 students in 2018/2019 academic year. Data about students’s knowledge competencies were collected by the test method and data about students’s skill were collected by observation methods, then the data were analyzed descriptively. The results show the fact that (1) there was an increase in students’s knowledge from 74.71 with sufficient predicate and classical completeness of 82.35% in the first cycle to an average of 82.00 and 100% learning completeness in the second cycle with good predicate. (2) In the Skill Competency, the average score of students’s in the first cycle was 69.67 with enough predicate in the first cycle to be an average of 80.52 with a good predicate which mean the score increase about 10.85 in skill competency. It consists the enhancement of enough predicate from 11.76% to 17.65% which mean the increase was about 5.89%. From the good predicate to very good and the increase was 11.73%. Thus through the application of the learning model of learning assisted by PhET media in learning is an effective alternative strategy to improve the competence of students of class XI Science one at SMA Negeri 1 Tampaksiring.   Penelitian ini bertujuan untuk meningkatan kompetensi pengetahuan dan keterampilan siswa, melalui penerapan pembelajaran discovery learning berbantuan media PhET (Physics Education And Technology) pada pembelajaran fisika. Jenis penelitian ini adalah penelitian tindakan kelas, yang terdiri dari dua siklus. Penelitian ini dilaksanakan di kelas XI IPA1 SMA Negeri 1 Tampaksiring dengan melibatkan 34 orang siswa tahun pelajaran 2018/2019. Data tentang kompetensi pengetahuan siswa dikumpulkan dengan metode tes, data tentang kompetensi keterampilan siswa dikumpulkan dengan metode observasi, Selanjutnya data dianalisis secara deskriptif. Temuan penelitian ini menunjukkan bahwa: (1) terjadi peningkatan pengetahuan siswa dari 74.71 dengan predikat cukup dan ketuntasan klasikal 82,35% pada siklus I menjadi rata-rata 82,00 dan ketuntasan belajar 100 % pada siklus II dengan predikat baik; (2) Pada Kompetensi Keterampilan nilai rata rata siswa pada siklus I 69,67 dengan predikat cukup pada siklus I menjadi rata rata 80,52 dengan predikat baik.Terjadi peningkatan sebesar 10,85 pada kompetensi keterampilan yang terdiri dari peningkatan dari predikat cukup sebesar 17,65%, pada silus 1 menjadi 11.76%. terjadi peningkatan sebesar 5,89% dari predikat baik menjadi sangat baik terjadi peningkatan sebesar sebesar 11,73% . Dengan demikian melalui penerapan model pembelajaran discovery learning berbantuan media PhET dalam pembelajaran merupakan strategi alternatif yang efektif untuk meningkatkan kompetensi siswa kelas XI IPA di SMA Negeri 1 Tampaksiring.